Nonmonotonic piezoresistive effect in elastomeric composite films. Issue 23 (24th February 2016) - Paliy, M.; Trebicky, T.; Guo, Q.; Kobe, B.; Suhan, N.; Arsenault, G.; Ferrari, L.; Yang, J.
ABSTRACT: We compared the change of electrical resistance with elongation (piezoresistive effect) in thin films made of conductive multiwalled carbon nanotubes embedded in eight different elastomers. Two distinct forms of piezoresistive effect were observed: (i) in the "monotonic" (M) case, the film resistance always increased with the applied strain; (ii) the "nonmonotonic" (NM) case showed an initial increase in the resistance, while with further elongation the resistance began to decrease. By varying the amount of nitrile and/or styrene groups in the polymer matrix one can alter the piezoresistive effect qualitatively: composites with ∼25 wt % or more of nitrile or styrene functional side groups exhibited M piezoresistance, while others, with no, or methyl side groups only, showed NM piezoresistance. Influence of the second filler (either conductive carbon black or nonconductive nanoclay) in the ternary composites on the piezoresistive effect was explored. The possibility to modify the piezoresistive behavior of the conductive elastomer composites, for example, via chemical modification of the polymeric matrix, opens up a new venue for practical applications such as diverse types of sensors and, in NM case, complex dynamical systems (bistable elements, electromechanical oscillators, etc.) in the MEMS field. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43518. Abstract :